1980
DOI: 10.1007/bf00009847
|View full text |Cite
|
Sign up to set email alerts
|

The taxonomy of Capillaria spp. (Nematoda: Trichuroidea) in carnivorous mammals from Ontario, Canada

Abstract: IntroductionFour species of Capillaria were found in eight species of wild carnivorous mammals (286 carcasses) taken in Ontario, Canada. C. plica was found in the urinary bladder of raccoon (Procyon lotor), red fox (Vuipes vulpes), coyote (Canis latrans), fisher (Martes pennanti) and striped skunk (Mephitis mephitis); C. putorii in the stomach and intestine of short-tailed weasel (Mustela erminea), mink (M. vison), fisher, marten (Mattes americana), striped skunk and raccoon; C. aerophila in the mucosa of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
5

Year Published

1981
1981
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 31 publications
3
44
0
5
Order By: Relevance
“…1). The pits on E. boehmi eggs are of different sizes and are generally round to oval, which is different from the netted appearance of eggs of E. aerophilus (Supperer 1953;Butterworth and Beverley-Burton 1980;Campbell 1991;Campell and Little 1991;Schoning et al 1993;Romashov et al 2000;Conboy 2009;Traversa et al 2010;Magi et al 2012).…”
Section: Fig 1 Egg Shell Morphology Of Eucoleus Boehmi and Eucoleusmentioning
confidence: 92%
See 1 more Smart Citation
“…1). The pits on E. boehmi eggs are of different sizes and are generally round to oval, which is different from the netted appearance of eggs of E. aerophilus (Supperer 1953;Butterworth and Beverley-Burton 1980;Campbell 1991;Campell and Little 1991;Schoning et al 1993;Romashov et al 2000;Conboy 2009;Traversa et al 2010;Magi et al 2012).…”
Section: Fig 1 Egg Shell Morphology Of Eucoleus Boehmi and Eucoleusmentioning
confidence: 92%
“…A few studies based on post mortem analysis of cardiopulmonary organs in foxes included steps of examining the nasal and cranial sinuses (Table II), leaving a gap in our knowledge on E. boehmi prevalence that might be under estimated (Campbell and Little 1991;Manas et al 2005). Periodical egg (Supperer 1953;Butterworth and Beverley-Burton 1980;Campbell 1991;Campell and Little 1991;Schoning et al 1993;Moravec 2000;Romashov et al 2000;Conboy 2009;Traversa et al 2010;Di Cesare et al 2012). Size range of length (black) and width (grey) of trichuroid eggs commonly recovered in many carnivore species.…”
Section: Fig 1 Egg Shell Morphology Of Eucoleus Boehmi and Eucoleusmentioning
confidence: 99%
“…11,15 One epidemiological study in Canada showed that as many as 67.2% of foxes in New Brunswick and Nova Scotia and 44% in Ontario were parasitized with E. aerophilus. 3,14 Infected animals suffered chronic respiratory disease with poor growth and decreased fur quality. Heavy infections could lead to significant mortality because of bronchopneumonia.…”
Section: Crenosoma Vulpis and Eucoleus Aerophilus (Formerly-mentioning
confidence: 99%
“…This finding was consistent with a study that reported 66% of the E. aerophilus worm burden was recovered from the trachea of infected red foxes. 3 The possibility exists that postmortem parasitic migration may have biased the location in which the 2 parasites were microscopically seen in airways. 13 Postmortem migration was not a likely concern for E. aerophilus because this nematode was typically embedded in the bronchial mucosa as reported previously by others.…”
Section: Crenosoma Vulpis and Eucoleus Aerophilus (Formerly-mentioning
confidence: 99%
“…Diagnosis after Butterworth & Beverley-Burton (1980) Trichuroidea Railliet, 1916Trichuridae Railliet, 1915;Capillariinae Railliet, 1915. Small nematodes, body filiform.…”
Section: Genusmentioning
confidence: 99%